PERANCANGAN DESAIN INTERIOR MUSEUM DENGAN TEKNIK INTERAKTIF SEBAGAI RUANG PUBLIK MASA KINI - Polniwati Salim; Christianto R; Sri Rachmayanti (Universitas Trisakti, 2018)
Abstract This study aims to analyze a museum interior design to be able to find the latest output regarding displaying or circulation techniques in a public space, especially museum. This study background is a public phenomenon visited by museums nowadays, which is seen on their social media accounts. Especially for contemporary and art design museums, it becomes an attractive icon for young people, as well as seniors. However, there are many things that need to be considered in designing a museum interior where many factors support for a success interior design, including: display techniques, gallery categorization, signage systems, and lighting. This study will examine how to applied the above items. As a comparison, contemporary art museums in Jakarta and New York. By doing these comparisons, researcher expected there will be a resume on how designing a good contemporary art museum. With good and attractive interior design in a contemporary art museum, it will further increased visitors interest and the awareness of the community to explore the museum. The method used is by observing and documenting techniques and analyzing the interior of research objects, combined with literature studies, hopefully this research can contribute to the museum design technique as an ergonomic and interactive public space for the wider community. For future development of the museum, this research contributes for a better, good and friendly display techniques. Abstrak Penelitian ini bertujuan untuk menganalisa perancangan interior sebuah museum untuk dapat ditemukan luaran terbaru perihal teknik display maupun sirkulasi dalam sebuah ruang publik yakni museum. Latar belakang penelitian adalah fenomena masyarakat luas yang terlihat kesadaran untuk berkunjung ke museum, yang terlihat pada akun sosial media masyarakat jaman sekarang yang demikian semarak, khususnya untuk museum bernafaskan contemporary dan art design, menjadi satu ikon menarik bagi kalangan muda, juga para senior. Namun demikian banyak hal yang perlu diperhatikan pada perancangan sebuah interior museum dimana banyak factor yang mendukung kesuksesan sebuah desain museum, antara lain dalam hal teknik display, pengkategorian gallery, system signage, maupun pencahayaan. Dengan design interior yang baik dan menarik pada sebuah museum kontemporer, diharapkan akan semakin menaikkan minat para pengunjung dan kesadaran masyarakat akan semakin meningkat untuk mengeksplorasi isi dari museum tersebut. Metode yang digunakan adalah dengan teknik pengamatan dan pendokumnetasian serta analisa interior objek penelitian, dipadukan dengan studi literature, diharapkan penelitian ini memberikan kontribusi pada teknik perancangan museum sebagai sebuah ruang public yang ergonomis dan interaktif menyenangkan bagi masyarakat luas. Untuk pengembangan museum ke depannya, penelitian ini memberikan sumbangsih perihal teknik display yang baik dan bersahabat